Quantification of Intramyocardial Metabolites by Proton Magnetic Resonance Spectroscopy - Gillinder, Lisa; Goo, Shi Yi; Cowin, Gary; Strudwick, Mark; van der Geest, Rob J.; Wang, William Y. S.; Ng, Arnold C. T. (Frontiers in Cardiovascular Medicine, 2015)
Purpose: To define intramyocardial triglyceride (TG) creatine (Cr) and choline (Cho) in healthy volunteers, and determine the feasibilities, scan durations and agreements between cardiac proton magnetic resonance spectroscopy ([1H]-MRS) performed with fewer signal averages versus a reference standard with 128 signal averages. Materials and Methods: Thirty-one participants underwent [1H]-MRS using 16, 32, 64 and 128 signal averages. Intramyocardial TG or Cr or Cho contents relative to water were calculated and expressed as a percentage. Results: Mean intramyocardial TG, Cr and Cho were 1.30±1.13%, 0.19±0.18% and 0.24±0.28% respectively. The feasibilities for quantifying intramyocardial TG, Cr and Cho using fewer signal averages ranged from 93.5–100%, 90.3–93.5% and 90.3–96.8% respectively. Scan durations for 16, 32, 64 and 128 signal averages were 1.1±0.5min, 2.6±0.9min, 5.9±2.0 min and 13.2±4.5min respectively (p<0.001). Agreements with the reference standard 128 signal average was higher for quantification of intramyocardial TG compared to Cr and Cho. Conclusions: Quantification of intramyocardial TG with [1H]-MRS with only 64 signal averages was highly feasible, showed excellent agreement with 128 signal averages, and had significantly shorter scan duration. In contrast, quantifying Cr and Cho using fewer signal averages had lower feasibilities and agreements compared to 128 signal averages.